A Distributed Virtual Learning Center in Cyberspace - Christos Bouras; A Philopoulos; D Fotakis (4th International Conference on Virtual Systems and Multimedia, Gifu, Japan, Vol. 2, 1998)
In this paper, we present a user-friendly 3D Distributed Virtual Environment (DVE) that would be used for on-line access to educational multimedia material over the Internet. We design and develop this application and the corresponding Graphical User Interface (GUI) in the framework of the European project “Virtual European School” (VES) whose aim is to develop a comprehensive resource of teaching material for secondary school education and to provide access to this material over Internet. It is a web-based application that is being developed as a client/server architecture using standard protocols and technologies such as TCP/IP, HTTP, HTML, Java and appropriate 3D formats.